Art in your world - Brommer, Gerald F.; Horn, George F. (Worcester, Mass. : Davis Publications, 1977)
Introduces the design principles, tools, materials, and techniques used by artists to express their ideas in two- and three-dimensional forms.
Includes index.
Bibliography: p. 278-281.
Keywords: Art -- Psychology -- Juvenile literature; Artists -- Psychology -- Juvenile literature; Visual perception -- Juvenile literature; Art -- Technique -- Juvenile literature; Art -- Technique; Visual perception